Patterns of clinical nail appearances in patients with cutaneous psoriasis - MARINA, ELENA MIHAELA (Clujul Med, 2017)
BACKGROUND AND AIM: Nail manifestations are often an overlooked aspect in psoriatic disease, cutaneous and joint involvement being far more often reported and investigated. The reported prevalence of nail changes varies in literature, specific fingernail clinical features having different degrees of occurrence. The aim of this study was to describe specific clinical patterns of fingernail alterations in adult patients with plaque-type psoriasis in a university hospital in the North-West of Romania. METHODS: Clinical data of 35 patients with fingernail psoriasis were collected and analyzed. Psoriasis Area and Severity Index (PASI) and Nail Psoriasis Severity Index (NAPSI) scores were used to quantify disease extension in each patient. RESULTS: PASI score proved linearly correlated with NAPSI score (p<0.05). The age of onset of fingernail psoriasis was positively correlated with age of onset cutaneous psoriasis (p<0.0001). Furthermore, the duration of cutaneous involvement and NAPSI proved significantly related (p<0.05). The third fingernail in the right hand and first fingernail in the left hand were in most of the cases severely affected. The most common observed nail pattern was pitting, followed by salmon patches and subungual hyperkeratosis. CONCLUSION: Important nail changes appear even in moderate forms of cutaneous psoriasis. Particular localization of specific fingernail psoriasis pattern enables the possibility of detecting early stage disease.